Flexible manufacturing benefit for the low-inventory factory - Lenz, J. E. (John E.) (Manufacturing engineering and materials processing (Marcel Dekker, Inc.), 1989)
Providing the basis for a formal flexible manufacturing design procedure, effective color graphics animation of simulation, and an economoc model for inverstment decisions, this important reference takes a fresh look at flexible manufacturing, going beyond computerization and mechanization to develop a unique technology.